2022
DOI: 10.1002/rth2.12653
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated venous thromboembolism in Israel: Incidence, risk factors, treatment, and health care utilization in a population based cohort study

Abstract: Background Recent international guidelines recommend thromboprophylaxis in patients with cancer at intermediate‐high venous thromboembolism (VTE) risk. Objectives We aimed to assess the current incidence, risk factors and management of cancer‐associated VTE and associated health care resource utilization in a 2.5‐million‐member state‐mandated health service in Israel. Methods Patients aged ≥18 years with newly diagnosed cancer, initiating sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Several other studies have reported similar findings. 5 21 22 However, some studies have reported prescription frequencies of DOACs of up to 50% as initial treatment in patients with CAT. 23 24 25 A lower proportion of patients with gastrointestinal or genitourinary malignancies and defining active cancer as cancer diagnosed up to 5 years preceding the thrombosis may be possible explanations for the higher DOAC prescription rate in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other studies have reported similar findings. 5 21 22 However, some studies have reported prescription frequencies of DOACs of up to 50% as initial treatment in patients with CAT. 23 24 25 A lower proportion of patients with gastrointestinal or genitourinary malignancies and defining active cancer as cancer diagnosed up to 5 years preceding the thrombosis may be possible explanations for the higher DOAC prescription rate in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported similar findings regarding increased DOAC prescription. 5 However, no data were presented for treatment patterns according to cancer sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accounting for differences in study design, CAT occurrence appeared to have geographic variations. Among representative studies at the time of initial cancer diagnosis, the 12-month cumulative incidence of CAT was 4.5% in 1 study (USA), 9 2.3% in 2 studies (Denmark, Israel), 10,12 and 0.5% in 2 studies (Taiwan, Japan). 6,13 One additional cohort study from Harris County, USA reported a higher incidence of 8.1% PE/LE-DVT at 12 months, 8 though the patient population was diverse (50% Hispanic, 28% Black), young (mean age 54), uninsured (74%) and living in disadvantaged neighborhoods (84%), and with more aggressive cancer and advanced stage (48%).…”
Section: Incidence Of Cancer-associated Thrombosis By Cancer Stage/tr...mentioning
confidence: 95%
“…1 A recent large registry study showed higher rates of mortality, recurrent VTE, and bleeding in patients with active cancer when compared with patients with a history of cancer or no cancer. 2 Sharman Moser et al 3 compared patients with cancer with and without VTE and found those with VTE were more likely to be hospitalized (81.4% vs 35.2%), had longer hospital stays (20.1 days vs 13.1 days), and were more likely to visit the emergency room (41.5% vs 19.3%). Studies have shown a 39.5% increase in total healthcare costs in ambulatory patients with lung cancer and VTE, 4 as well as increased healthcare utilization, a 3-fold increase in the rate of hospitalization, and an annual increase in per-patient cost of approximately $29,000 for recurrent VTE.…”
mentioning
confidence: 99%